2020
DOI: 10.1186/s13244-019-0833-4
|View full text |Cite
|
Sign up to set email alerts
|

Imaging spectrum of abnormal subcutaneous and visceral fat distribution

Abstract: Adipose tissue plays multiple and complex roles not only in mechanical cushioning and energy storage but also as an important secretory organ that regulates energy balance and homeostasis multilaterally. Fat tissue is categorized into subcutaneous fat tissue (SCAT) or visceral fat tissue (VSA) depending on its distribution, with the two having different metabolic functions. Near-total lack of fat in congenital/acquired generalized lipodystrophy, cachexia, or any other severe malnutrition condition induces seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 75 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…The definite reason SAT alone rapidly decreased just after introducing sorafenib in advance of skeletal muscle and VAT remains unclear. SAT is known to act as metabolic storage that can accumulate superfluous energy [ 24 ]. Therefore, we consider that SAT might first be used as an energy source when a negative energy balance is induced by sorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…The definite reason SAT alone rapidly decreased just after introducing sorafenib in advance of skeletal muscle and VAT remains unclear. SAT is known to act as metabolic storage that can accumulate superfluous energy [ 24 ]. Therefore, we consider that SAT might first be used as an energy source when a negative energy balance is induced by sorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, however, it may be difficult to determine whether a lipoma is present at a location of symptoms. 19 …”
Section: Discussionmentioning
confidence: 99%
“…In some cases, however, it may be difficult to determine whether a lipoma is present at a location of symptoms. 19 Imaging characterization of any potential mass requires documentation of additional secondary features such as location, displacement or invasion of adjacent structures, and reaction of surrounding tissues. Correlation for pain or a palpable mass is also clinically important when the imaging features are worrisome.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with other medical conditions that are characterized by generalized abnormal fat distribution, such as eating disorders. For example, Yamamoto et al showed diminished subcutaneous fat and diffuse T1 hypointense marrow signal in an individual with bulimia nervosa [5] . Kraeft et al reported that individuals with severe anorexia nervosa demonstrate loss of fat signal in both bone marrow and subcutaneous tissues on MRI [6] .…”
Section: Discussionmentioning
confidence: 99%
“…3 ). Residual subcutaneous and visceral fat were found in classic locations of brown adipose tissue (axilla, supra- and infraclavicular fossa, around solid organs) and demonstrated increased density, which is thought to reflect smaller fat cell size with inflammatory/edematous change during lipolysis [5] . This patient declined treatment and died 2 months later with palliative measures.…”
Section: Case Reportmentioning
confidence: 99%